The Expertise Of Muhammad Al-Hafizh Al-Misri At-Tijani (1897-1978) In Hadith - Ilyas Jamil, Muhammad; Tajul Arifin; Engkos Kosasih (Tabayyun : Journal Of Islamic Studies, 2024)
This writing aims to examine the prolific aspects and biography of one of the remarkable lives and multifaceted scholarly endeavours of Sayyid Muhammad al-Hafiz al-Misri at-Tijani, a towering figure in Islamic scholarship in Egypt during the late 19th century. Revered as a Muhaddith[1], Mufassir, Mutasawwif, and Mujahid, he exemplified a profound spiritual connection alongside an unparalleled commitment to the preservation and dissemination of Islamic knowledge. Born into a noble lineage, his scholarly pursuits took him across the Islamic world, where he garnered authority from renowned scholars and meticulously preserved rare manuscripts. A passionate lover of hadith, he dedicated himself to the exhaustive verification and organisation of foundational texts, enhancing their accessibility for future generations. Furthermore, his instructional efforts, notably his recurrent teachings of Sahih Bukhari, earned him the esteemed title of Master of the Muhaddiths. Beyond scholarship, he valiantly defended Islam against colonial onslaughts, employing both his intellectual prowess and military acumen. Endowed with miraculous abilities, his legacy transcends time, serving as a beacon of spiritual enlightenment and scholarly excellence for generations to come.